Autoimmune-Associated Hemophagocytosis and Myelofibrosis in a Newly Diagnosed Lupus Patient: Case Report and Literature Review - Deonne Thaddeus V. Gauiran; Paula Victoria Catherine Y. Cheng; Christopher Ryan P. Pagaduan; Maria Clariza M. Santos (Case Reports in Hematology)
Bone marrow abnormalities in SLE are now becoming increasingly recognized, suggesting that the bone marrow may also be an important site of target organ damage. In this study, we present a rare case of concurrent autoimmune hemophagocytic syndrome and autoimmune myelofibrosis, potentially life-threatening conditions, in a newly diagnosed SLE patient. We report a case of a 30-year-old Filipino woman who presented with a one-year history of fever, constitutional symptoms, exertional dyspnea, joint pains, and alopecia and physical examination findings of fever, facial flushing, cervical lymphadenopathies, and knee joint effusions. Laboratory workup revealed pancytopenia with leukoerythroblastosis, elevated ESR, increased serum levels of transaminases, elevated CRP and LDH, hyperferritinemia, hypertriglyceridemia, proteinuria, hepatomegaly, and positive antinuclear antibody. Bone marrow aspiration and trephine biopsy revealed hemophagocytosis and moderate myelofibrosis. The patient was diagnosed with SLE with concomitant autoimmune-associated hemophagocytic syndrome and autoimmune myelofibrosis. Treatment with high-dose corticosteroids led to dramatic clinical improvement with normalization of laboratory data and complete resolution of bone marrow hemophagocytosis and myelofibrosis. Hemophagocytosis and myelofibrosis, although uncommon, are possible initial manifestations of SLE and should be included in the differential diagnosis of cytopenias in SLE. Thorough clinical assessment and microscopic bone marrow examination and timely initiation of corticosteroid therapy are essential in the diagnosis and management of these potentially life-threatening conditions. This case emphasizes that the bone marrow is an important site of target organ damage in SLE, and evaluation of cytopenias in SLE should take this into consideration.